Remote sensing evaluation of Cape parrot habitat in the Eastern Cape: implications for conservation - Wright, Emma (Department of Biological Sciences, 2023)
The Cape parrot is the only endemic parrot of South Africa and is currently nationally threatened. One of the biggest threats to the Cape parrot is the past and present degradation of indigenous forest. The Amathole Mistbelt Forest in the Eastern Cape is the primary habitat for Cape parrot and has historically been heavily degraded. In order to conserve the Cape parrot effectively, there is a need to understand the spatial distribution of indigenous forest patches and their quality. There is currently not a sufficiently accurate landcover map available to fulfil this need. Thus, this study uses remotely sensed imagery at a 10 m resolution and random forest classification to (1) produce a land cover map of the indigenous forest in the Amathole region; (2) determine habitat quality of the indigenous forest, and (3) determine whether forest loss, as reported by Global Forest Watch (GFW), reflects the loss of indigenous forest or the clearing of plantations and woody alien invasives. The overall accuracy of the classification was very high at 82%. Cross validated accuracies were all high ranging from 95 – 100%, with water having the highest accuracy and indigenous forest, eucalyptus spp., pine spp., and infrastructure having the lowest accuracies. F1 scores ranged from 0.78 – 1.0, with indigenous forest ranking the second lowest at 0.80 and grassland ranking the second highest at 0.91. Indigenous forest covered 26% of the study area. Black wattle, pine spp. and eucalyptus spp. covered a combined 35% of the study area. The detailed map of indigenous forest shows the extent of its fragmentation and outlines some of the management implications associated with small forest patches. Secondly, habitat quality for Cape parrot is questioned as there is a lack of emergent canopy tree species and 30% of the matrix between forest patches is invaded by invasive alien species. Thus, it is suggested that a strong focus is put into clearing and managing invasive alien species. Lastly, GFW ‘forest cover loss' is shown to be comprised primarily of plantation felling and invasive clearing. It is suggested that there has been little loss of indigenous forest in the last 30 years. Further research will include creating an open and accessible product in the form of a Google Earth Engine App to share with conservation managers in the area.